Predictors of early adulthood hypertension during adolescence: a population-based cohort study - Saeed Kalantari; Davood Khalili; Samaneh Asgari; Noushin Fahimfar; Farzad Hadaegh; Maryam Tohidi; Fereidoun Azizi (BMC, 2017)
Abstract Background Some longitudinal studies have shown that blood pressure tracks from adolescence to adulthood, yet there is limited evidence regarding the predictive factors of adulthood hypertension during adolescence. This study was conducted within the framework of the Tehran Lipid and Glucose Study (TLGS) to investigate the role of some factors in adolescence, measured in the first examination (1999-2001), to predict adulthood hypertension in the 4th examination (2009-2011). Methods Overall, 1579 subjects, aged 10-19 years, were used for the analysis of the current study. Mean age (SD) of participants at the baseline was 14.2 (2.5) years and 55% of them were female. A forward stepwise approach (p-value <0.2 for enter and >0.05 for removal) was considered to keep significant covariates among common variables including gender, body mass index, waist circumference, wrist and hip circumferences, fasting blood sugar, triglycerides, high density lipoprotein cholesterol, total cholesterol (TC), systolic (SBP) and diastolic blood pressure (DBP). Variance inflation factor (VIF) showed some multicollinearity for anthropometric variables (VIFs between 3.5 and 10). Multivariable logistic regression revealed that gender, blood pressure, wrist circumference and total cholesterol in adolescents are important predictors for adulthood hypertension. Results The risk increased by 4% and 39% per each 10 mmHg and 1 mmol/L increase in SBP/DBP and TC, respectively; additionally, females had a 70% lower risk. Among anthropometric variables, wrist circumference remained in the model, with 50% per centimeter increase in the risk of hypertension. Conclusions Wrist circumferences and TC had significant roles in predicting hypertension through adolescence to adulthood.